σ-Thienyl complexes of palladium(II), trans-PdBr(C4H4-nBrn-1S-C)(PPh3)2(n = 1-4), from oxidative addition of bromothiophenes to Pd(PPh3)4. X-ray structural identification of key intermediates of catalytic debromination of 2-bromothiophene and tetrabromothiophene - Xie, Y. (2014)
Journal of Organometallic Chemistry